Comprehensive Analysis of Bacterial Community Structure and Diversity in Sichuan Dark Tea (Camellia sinensis) - Yan, Kuan; Yan, Linfeng; Meng, Lina; Cai, Hongbing; Duan, Ailing; Wang, Lian; Li, Quanzi; El-Sappah, Ahmed H.; Zhao, Xianming; Abbas, Manzar (Frontiers in Microbiology, 2021)
Bacteria and fungi present during pile-fermentation of Sichuan dark tea play a key role in the development of its aesthetic properties, such as color, taste, and fragrance. In our previous study, high-throughput sequencing of dark tea during fermentation revealed Aspergillus was abundant, but scarce knowledge is available about bacterial communities during pile-fermentation. In this study, we rigorously explored bacterial diversity in Sichuan dark tea at each specific stage of piling. Analysis of cluster data revealed 2,948 operational taxonomic units, which were divided into 42 phyla, 98 classes, 247 orders, 461 families, 1,052 genera, and 1,888 species. Certain members of the family Enterobacteriaceae were dominant at early stages of fermentation YC, W1, and W2; Pseudomonas at middle stage W3; and the highest bacterial diversity was observed at the final quality-determining stage W4. Noticeably, probiotics, such as Bacillus, Lactobacillus, Bifidobacterium, and Saccharopolyspora were also significantly higher at the quality-determining stage W4. Our findings might help in precise bacterial inoculation for probiotic food production by increasing the health benefits of Sichuan dark tea. This research also falls under the umbrella of the “Establish Good Health and Well-Being” Sustainable Development Goals of the United Nations Organization.